Landscape and garden design sketchbooks - Richardson, Tim, 1968- (London : Thames & Hudson, 2015)
Featuring hundreds of drawings and illustrations as diverse as their creators, this book intends to be a source of inspiration for planting, design elements, colour schemes and materials, encouraging weekend gardeners, design professionals and students to draw their ideas by hand
engineering bookfair2016
Keywords: Landscape architectural drawing